ALUMNI GIVING : AN EXAMINATION OF COMMUNICATION AND SOLICITATION PREFERENCES AT A PUBLIC UNIVERSITY IN NORTH CAROLINA - Afolayan, LaTanya D. (East Carolina University, 2012)
Unless there are adequate communication and solicitation tools, college and university leaders are unable to maximize sufficient levels of support from alumni. If it is determined that alumni respond differently to various types of communication, college and university administrators can streamline and segment the flow of information more appropriately. This study offered a view of alumni communication and solicitation preferences and explored whether there were differences in preferences based on age, gender, ethnicity, marital status, educational and income levels. This study may offer university presidents, chancellors and advancement professionals with theoretical and practical information to develop and maintain effective communication and solicitation strategies for their alumni.   The Chi-square Test of Independence was utilized to examine whether there were differences in alumni communication and solicitation preferences and the following independent variables - age, gender, ethnicity, marital status, educational and income levels. The Chi-Square Test of Independence revealed an association between alumni solicitation preferences and age. The Chi-square Test of Independence revealed an association between the type of communication preference and age. There was also a significant association related to the preferred frequency of communication and the independent variables of age, gender, and income. The final question in this study was designed to explore whether the receipt of information had an impact on alumni giving decisions. The Chi-square Test of Independence did not reveal a significant association between the receipt of information, giving decisions, and the independent variables - age, gender, ethnicity, marital status, educational and income levels.
Keywords: Educational leadership; Alumni communications; Alumni giving; Educational fund raising--North Carolina; Universities and colleges--North Carolina--Finance; Universities and colleges--Alumni and alumnae--North Carolina; Appalachian State University--Alumni and alumnae